Developing the Statutory Obligation of Good Faith in Employment Law: What Might Human Resource Management Contribute? - Anderson, Gordon; Bryson, Jane (Victoria University of Wellington Law Review, 2006)
The Employment Relations Act 2000 has strengthened individual employee rights in two ways. First, it provides that the parties to an employment relationship must deal with each other in good faith. Secondly, it has made it clear that the standard by which an unjustifiable action is to be judged is an objective one. It is suggested that applying these new provisions will require some realignment of the judicial mindset which has tended to resist interventions into an employer's management of its employees. This article will first discuss the nature and extent of the good faith obligation in the management of the day-to-day individual employment relationship as well as the nature of the changes to the test of justification. It will then go on to consider whether disciplines such as organisational psychology and human resource management good practice provide a potential source of reliable evidence which can contribute to the legal development and re-evaluation of concepts such as good faith and justification. The ability to make such a contribution is dependent on whether the disciplines are sufficiently developed and their principles and practices sufficiently accepted, and also on whether the courts are prepared to accept and give adequate weight to expert evidence that may be adduced.